Antibiotic use patterns in endoscopic sinus surgery: a survey of the American Rhinologic Society membership. Issue 4 (15th January 2018) - Fang, Christina H.; Fastenberg, Judd H.; Fried, Marvin P.; Jerschow, Elina; Akbar, Nadeem A.; Abuzeid, Waleed M.
Abstract : Background: There is a paucity of data supporting antibiotic use in endoscopic sinus surgery (ESS). The objective of this study is to determine perioperative antibiotic use patterns and factors which influence use in ESS. Methods: An online‐based survey was distributed to members of the American Rhinologic Society (ARS). Outcomes included timing of perioperative antibiotic use, practice environment, years of experience, and patient factors that influenced antibiotic use. Results: There were 204 responses (response rate 18.3%); 36.8% of respondents were in academic positions, 32.8% were in private practice, and 30.4% were in academic‐affiliated private practice; 20.6% routinely gave preoperative antibiotics, most commonly to reduce bacterial burden (59.5%) and mucosal inflammation (59.5%); 54.4% routinely gave intraoperative antibiotics, most commonly to reduce the risk of postoperative infection (63.1%); 62.3% routinely gave postoperative antibiotics, citing the need to reduce the risk of postoperative infection (75.6%). Diagnosis influenced postoperative antibiotic use in 63.0%. Preoperative antibiotics were more likely to be prescribed by respondents with more than 5 years of experience (odds ratio [OR] 2.97; 95% confidence interval [CI], 1.04 to 8.54; p  = 0.043). Compared to private practitioners, academicians were more likely to give intraoperative antibiotics (OR 2.68; 95% CI, 1.39 to 5.17; p  = 0.003), but not preoperative or postoperative antibiotics. Use of nonabsorbable packing was significantly associated with use of postoperative antibiotics (OR 2.01; 95% CI, 1.07 to 3.77; p  = 0.031). Conclusion: This study demonstrates the significant variation in perioperative antibiotic use among otolaryngologists. These results provide support for the establishment of evidence‐based practice guidelines for perioperative antibiotic use in ESS.